MicroRNA-9-1 Attenuates Influenza A Virus Replication via Targeting Tankyrase 1 - Gayan Bamunuarachchi; Kishore Vaddadi; Xiaoyun Yang; Quanjin Dang; Zhengyu Zhu; Sankha Hewawasam; Chaoqun Huang; Yurong Liang; Yujie Guo; Lin Liu (Karger Publishers, 2023)
An unstable influenza genome leads to the virus resistance to antiviral drugs that target viral proteins. Thus, identification of host factors essential for virus replication may pave the way to develop novel antiviral therapies. In this study, we investigated the roles of the poly(ADP-ribose) polymerase enzyme, tankyrase1 (TNKS1) and the endogenous small noncoding RNA, miR-9-1 in influenza A virus (IAV) infection. Increased expression of TNKS1 was observed in IAV-infected human lung epithelial cells and mouse lungs. TNKS1 knock-down by RNA interference repressed influenza viral replication. A screen using TNKS1 3'-untranslation region (3'-UTR) reporter assays and predicted microRNAs identified that miR-9-1 targeted TNKS1. Overexpression of miR-9-1 reduced influenza viral replication in lung epithelial cells as measured by viral mRNA and protein levels as well as virus production. miR-9-1 induced type I interferon production and enhanced the phosphorylation of STAT1 in cell culture. The ectopic expression of miR-9-1 in the lungs of mice by using an adenoviral viral vector enhanced type I interferon response, inhibited viral replication and reduced susceptibility to IAV infection. Our results indicate that miR-9-1 is an antiinfluenza microRNA that targeting TNKS1 and enhanced cellular antiviral state.